Ccd speckle observations of binary stars with the wiyn telescope. vi. measures during 2007-2008 - Horch, Elliott P.; Falta, David; Anderson, Lisa M.; DeSousa, Michael D.; Miniter, Craig M.; Ahmed, Tasmia; van Altena, William F. (The Astronomical Journal, 2009)
Results of 974 speckle observations of 546 binary stars are presented. Observations were obtained at the WIYN 3.5 m Telescope at Kitt Peak National Observatory during the time interval from 2007 January to 2008 June. In all cases, the relative separation and position angle of the components are measured, and the magnitude difference is determined in 809 cases. The precision of the results as judged from repeat observations and objects with very well-determined orbits is similar to previous papers in this series, namely ∼ 3 mas in separation and <1° in position angle in most cases. Similarly, the photometric precision remains consistent with previous WIYN speckle data, on average ∼ 0.1 mag per observation. Six systems of special interest are discussed. © 2010. The American Astronomical Society. All rights reserved.
58 citations (Crossref) [2023-10-31] Citation Key Alias: pop00066 tex.type: [object Object]
Keywords: Binaries: visual; Techniques: high angular resolution; Techniques: interferometric; Techniques:Photometric; dept.phy; peer-reviewed